PEMBUATAN ALAT PERAJANG SINGKONG DALAM PENINGKATAN PRODUKSI - Wahyu Wiguna; Diar Septiawan; Muhdisi Muhdisi; Petrus Canisius Adi S (Gapenas Publisher, 2023)
Cassava is a tuberous plant that can grow in the tropics with a hot and humid climate. Tropical climates are needed by cassava for its growth process so that this plant cannot grow at temperatures below 10ºc. Cassava is a tuber or tree root that can grow on sandy to clay soil, as well as on low fertility soil. The length of cassava ranges from 15-30 cm with a relatively different diameter as well, which is 2-5 cm. Cassava has a skin consisting of two layers, the first layer is the outer skin while the second layer is the inner skin with white or yellowish flesh. In its production so far cassava chopper still uses human labor (manual). It would be better if the production of cassava chopper increases without ignoring the existing human aspects. Therefore, a machine is needed as a human aid in increasing the productivity of cassava chopper. The significant increase after the experiment means that the cassava chopper machine is able to help the existing chopper process